Psychosocial Adjustment and Psychopathology of Men Sexually Abused During Childhood - Forouzan, Elham (International journal of offender therapy and comparative criminology, 2005)
The purpose of this study was to evaluate psychosocial adjustment and psychopathology among men sexually abused during their childhood and arrive at a better understanding of the reasons for which, following such sexual experiences, some adult males manifest greater distress than others. In total, 64 participants were interviewed and completed eight questionnaires covering various aspects of childhood and adult life. Results suggest the existence of three types of sexual abuse scenarios. Participants in each of these three groups presented with an adult-specific adjustment. However, the methodology and multivariate analyses used in this study suggest that some of these problems were not only associated with the sexual contacts but also with other childhood experiences and with the participant's cognitive, affective, and psychological resources